1978
DOI: 10.1901/jaba.1978.11-259
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social‐skills Training in the Treatment of Extreme Anxiety and Deficient Verbal Skills in the Job‐interview Setting

Abstract: A 30-year-old recent college graduate, exhibiting extreme anxiety and deficient verbal skills in job interviews, was treated with a social-skills training procedure that included instructions, modelling, behavior rehearsal, and videotape feedback. Three target behaviors-focused responses, overt coping statements, and subject-generated questions-were presented using a multiple-baseline design. Galvanic skin-response activity was monitored during pre-and posttraining in vivo job interviews. In addition, independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…This arrangement shows a new variant in the demonstration of functional relationships between behavioral changes and consequences in MBDs. Several studies in Tables 1 and 2 (for instance Clark et al, 1979;Hollandsworth et al, 1978;McGee et al, 1986;Riordan et al, 1984) show the utility of this variant of the MBD across behaviors (i.e. the MBD across exemplars) in the clinical context.…”
Section: Mbd Across Exemplars As An Alternative In Clinical Settingsmentioning
confidence: 99%
“…This arrangement shows a new variant in the demonstration of functional relationships between behavioral changes and consequences in MBDs. Several studies in Tables 1 and 2 (for instance Clark et al, 1979;Hollandsworth et al, 1978;McGee et al, 1986;Riordan et al, 1984) show the utility of this variant of the MBD across behaviors (i.e. the MBD across exemplars) in the clinical context.…”
Section: Mbd Across Exemplars As An Alternative In Clinical Settingsmentioning
confidence: 99%
“…However, the discussion group (which viewed filmstrips and discussed articles on interviewing) exhibited greater increases in length of speaking, ability to explain skills, and expression of feelings and personal opinions on matters relevant to the interview. Hollandsworth, Glazeski, and Dressel (1978) provided an in-depth analysis of a social-skills training program to teach job interview skills to a recent 30-year-old college graduate who exhibited extreme anxiety and deficient verbal interview skills. Using a multiple baseline design, interview training was conducted using such methods as modeling, behavioral rehearsal, feedback, viewing model videotapes, and role playing.…”
Section: Rehabilitation Clientsmentioning
confidence: 99%
“…Specific relevant aspects of verbal behaviour are fluency of speech (Sereno and Hawkins, 1967), appropriateness of content (Sigelman et al, 1980) and positive vs negative information (Jennings and Davis, 1977;Peters and Terborg, 1975). Other researchers found that applicants' nonverbal behaviour also influences the selection outcome, such as eye contact (Amalfitano and Kalt, 1977), head movements and smiling (Young and Beier, 1977), expressive hand-movements (Wexley et al, 1975) and composure (Hollandsworth et al, 1978). A study of Reis et al (1990) demonstrated that smiling persons were perceived to possess more positive traits than non-smiling persons.…”
mentioning
confidence: 99%